Characterization of Tauopathy in a Rat Model of Post-Stroke Dementia Combining Acute Infarct and Chronic Cerebral Hypoperfusion - Back, Dong Bin (Int J Mol Sci, 2020)
Post-stroke dementia (PSD) is a major neurodegenerative consequence of stroke. Tauopathy has been reported in diverse neurodegenerative diseases. We investigated the cognitive impairment and pathomechanism associated with tauopathy in a rat model of PSD by modeling acute ischemic stroke and underlying chronic cerebral hypoperfusion (CCH). We performed middle cerebral artery occlusion (MCAO) surgery in rats to mimic acute ischemic stroke, followed by bilateral common carotid artery occlusion (BCCAo) surgery to mimic CCH. We performed behavioral tests and focused on the characterization of tauopathy through histology. Parenchymal infiltration of cerebrospinal fluid (CSF) tracers after intracisternal injection was examined to evaluate glymphatic function. In an animal model of PSD, cognitive impairment was aggravated when BCCAo was combined with MCAO. Tauopathy, manifested by tau hyperphosphorylation, was prominent in the peri-infarct area when CCH was combined. Synergistic accentuation of tauopathy was evident in the white matter. Microtubules in the neuronal axon and myelin sheath showed partial colocalization with the hyperphosphorylated tau, whereas oligodendrocytes showed near-complete colocalization. Parenchymal infiltration of CSF tracers was attenuated in the PSD model. Our experimental results suggest a hypothesis that CCH may aggravate cognitive impairment and tau hyperphosphorylation in a rat model of PSD by interfering with tau clearance through the glymphatic system. Therapeutic strategies to improve the clearance of brain metabolic wastes, including tau, may be a promising approach to prevent PSD after stroke.